(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Recently, the problem of protection and rational use of the gene pool, including endemic and rare medicinal plants, remains a problem. The expansion of exploitation of plant resources has caused certain plant communities and their components to undergo changes, and some plant species are close to extinction. Changes in the habitat conditions of endemic and rare species under the influence of anthropogenic factors can lead to a reduction in the range. To preserve plant species whose state in nature is of serious concern, as well as for the rational use of plant resources, it is necessary to take into account all plant species that need protection.